Effect of Moringa Leaf Ethanol Extract on Reduced Levels of Mda, TNF-α and Description of Inflammatory Cells in Rat Sinus Mucosa Model of Acute Rhinosinusitis - Widi Wardani, Andriana Tjitria; Purwanto, Bambang; DonoIndarto, -; Wasita, Brian; Cilmiaty AR, Risya (Bangladesh Journal of Medical Science, 2022)
Background: Symptoms and signs of acute viral and bacterial rhinosinusitis that are not specific cause difficulties in diagnostic enforcement, causing difficulties in administering therapy, so often doctors provide antibiotic therapy on acute viral rhinosinusitis. Irrelevant antibiotics will cause frequent antibiotic resistance. Adjuvant therapy is required to prevent infections that continue to become chronic, shorten the duration of infection, and avoid unwanted complications. Moringa leaves (M. oleifera)contains antioxidant components that can help rebalance redox metabolism and reduce excess free radicals so as to prevent oxidative stress. Method: posttest only control group research design. Male strain Sprague Dawley white rat was maintained and treated at the Nutrition Laboratory of the Center for Food and Nutrition Studies of Gadjah Mada University (UGM). Mice were divided into 4 groups. Group 1: standard feed., group 2: standard feed and staphylococcus-induced aureus, group 3: standard feed, Staphylococcus aureus-induced given amoxicillin dose of 27 mg/day, group 4: standard feed, Staphylococcus aureus-induced was given amoxicillin dose of 27 mg/day and given (EEDK) 200 mg/KgBW/day. Data analysis Of Normality test using Shapiro-Wilk Test and homogeneity using Levene’s Test obtained results p>0.05. Then conducted One Way AnovaTest obtained p<0.05 and continued with post-hoc LSD test. The data is analyzed using SPSS 25.0 for Windows. Result: MDA test Anova obtained p value (Sig.) = 0.000 (p< 0.05), Post Hoc with LSD all groups (p-value) < 0.05, indicated a significant mean difference in average MDA levels among all groups. The lowest mean difference in MDA levels in group K with P3 was 0.92 pg/mL; while P1 with P3 has the largest average MDA rate difference of 7.47 pg/mL. TNF-α Anova test obtained p value (Sig.) = 0.000 (p< 0.05), Post Hoc with LSD of all groups (p-value= 0.000) < 0.05, there is a meaningful difference in the average level of TNF-α between all groups. The smallest average difference in TNF-α levels in group K with P3 was 0.31 pg/mL; while P1 with P3 has the largest average TNF-α rate of 5.01 pg/mL. Description of inflammation of the mucosa cavum rice and sinus K score 0; P1 score 3; P2 score 2; P3 score 1. Conclusion: Moringa leaf ethanol extract in this study can be used as adjuvant therapy because it can lower MDA and TNF-α levels in mice induced with Staphylococcus aureus along with amoxicillin standard therapy. Extract ethanol moringa leaves in this study can be used as adjuvant therapy because it can lower the score of inflammatory cells better than by only given standard therapy only Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 311-317